Electromagnetically shielding composite made from carbon fibers, glass fibers, and impact-resistant polypropylene: Manufacturing technique and evaluation of physical properties. (November 2014) - Lin, Ching-Wen; Lou, Ching-Wen; Huang, Chen-Hung; Huang, Chien-Lin; Lin, Jia-Horng
In order to create polymer composites that can shield machine and instrument casings from electromagnetism and to reclaim waste material, this study melt-blended impact-resistant polypropylene (PP) chips, carbon fibers (CFs; 5, 10, 15, or 20 wt%), and glass fibers (GFs; 0, 5, 7 wt%). This process used a single-screw extruder to make electrically conductive composites. The resulting composites were then evaluated in terms of mechanical properties, electromagnetic shielding effectiveness (EMSE), and surface resistivity. According to experimental results, an increase in CF content increased PP/CF composites' tensile strength to 29.31 MPa and flexural strength to 38.93 MPa but decreased the impact strength to 49.04 MPa. When the CFs were increased to 15 wt%, the EMSE and surface resistivity of PP/CF composites were above 20 db and 3.3 × 10 3 Ω/square. For PP/CF/GF composites, with an increase in GF content, the EMSE decreased and the surface resistivity increased.